Perancangan dan Implementasi Tracking Solar Cell System dengan Menggunakan Overload Protection - Agung Wijaya; Bengawan Alfaresi; Feby Ardianto (Fakultas Teknik, 2021)
Solar cell tracking system is a system that uses the latest technology with combining solar tracking, the intensity of sunlight absorbed by solar cells can be optimized automatically. The purpose of this study is to make the Arduino-based solar monitoring system and load protection tool. The device is also equipped with an LDR sensor that detects the presence of sunlight, sends data from the LDR to Arduino and delivers signals to linear actuators. When the charge supplied by the battery exceeds the capacity of the battery, the INA219 sensor detects overload and a signal sent to Arduino asking for a relay to release the load. The results showed that tracking solar cell systems were successful in improving the efficiency of solar cells with an average power yield of 0.87 ampere of 12.62 watts from before without tracking the average obtained 0.62 ampere 8.83 atts. The performance of the protection system indicates that the load is cut off when the charging current exceeds the specified limit of 2.6 ampere.